The Role of Language and Its Linguistic Impacts on Pan-African Cultural Development - Williams-Onyeji, Paulina Oluwafunmilayo (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study evaluated the formative influence of Pan Africanism in the role of language and its Linguistics impacts on Cultural Development. Language production is a culturally learned behavior as culture is a representative of language, culture is not only inseparably related to language, but also plays an important role throughout the process of its development because Pan-Africanism was a type of nationalism that fused traditional culture and modern ideology to generate social power that it was. However, the knowledge gained through the study will help unveiled many practical consequences of language and its linguistic impacts on Pan-African Cultural Development. The objective of this evaluation is to ascertain the role and the level of Pan Africanism influence on the formative content and advancement of cultural policy in Africa and to benefit the national and desporal cultural interest of Africans. The study adopted Historical Textual Analysis which is engaged in reviewing past documents, treaties, and declarations on African unity to track the evolution of language in Pan-African ideology. It is designed to employed qualitative analysis, consultation of vital hard and electronic books and journals. This paper establishes that Pan-Africanism remains vital in evolving with African nations aspirations through advocating for self cultural pride advancement, economic self sufficiency and polical emancipation.